Seni Membaca Al-Qur'an (Qira'at): Sejarah dan Perkembangan - Hamdani Anwar (Refleksi: Jurnal Kajian Agama dan Filsafat, 1999)
The discussion of qira'at is one of the most fundamental studies in Ulūm al-Qur’ān. This is closely related to various factors that can lead to various issues. The method of recitation is also considered as one of the proofs of the authenticity of the Qur’an. The fact proves that through authentic and even mutawatir narrations, the qira’at imams teach it meticulously and directly (musyafahah). Furthermore, in its implications, differences in recitation methods may lead to discrepancies in determining the legal rulings contained within a verse. Such biases may also occur in other aspects of Islamic teachings, such as creed, ethics, and others.